Javanese Marital Quality, Determinants Factors from Sex, Length of Marriage, Number of Children and Family Expenditure - Setiawati, Farida Agus; Nurhayati, Siti Rohmah (Jurnal Ilmu Keluarga dan Konsumen, 2020)
Perceptions and factors that make marriages qualified are differ from one region to another. This study aimed to describe the quality and examine the factors that determinants the quality of Javanese marriage, namely: gender, marriage age, number of children and monthly financing. A total of 579 Javanese husbands and wives from Yogyakarta, Surakarta, Banyumas, and Pekalongan involved in this research. Data were collected by a multistage random sampling technique, using the instrument of marriage quality, and analyzed descriptively and inferential. The results of this study indicate that most of the quality of Javanese marriages is classified as high, especially in the quality of well-being, while on the quality relationship between husband and wife, most of the Javanese people are in the medium category. It is no difference in the marital quality between husbands and wives. The marital quality as a whole is influenced by the number of children and monthly financing, as well as at the quality of relations between husband and wife. The quality of the well-being of husband and wife is not only influenced by the number of children and monthly financing but also the age of marriage.